2014
DOI: 10.1016/j.ijengsci.2014.02.031
|View full text |Cite
|
Sign up to set email alerts
|

Stability of an inflated hyperelastic membrane tube with localized wall thinning

Abstract: It is now well-known that when an infinitely long hyperelastic membrane tube free from any imperfections is inflated, a transcritical-type bifurcation may take place that corresponds to the sudden formation of a localized bulge. When the membrane tube is subjected to localized wall-thinning, the bifurcation curve would "unfold" into the turning-point type with the lower branch corresponding to uniform inflation in the absence of imperfections, and the upper branch to bifurcated states with larger amplitude. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 19 publications
0
9
0
2
Order By: Relevance
“…Thus, the accelerationr can be computed in terms of the accelerationä on the inner surface. By the governing equations (46), the condition (4) is valid for x = (r, θ, z) T , since…”
Section: Dynamic Radial-axial Deformation Of a Cylindrical Tubementioning
confidence: 99%
See 3 more Smart Citations
“…Thus, the accelerationr can be computed in terms of the accelerationä on the inner surface. By the governing equations (46), the condition (4) is valid for x = (r, θ, z) T , since…”
Section: Dynamic Radial-axial Deformation Of a Cylindrical Tubementioning
confidence: 99%
“…In this case, the integrand is negative for 0 < r 2 /R 2 < 1/α and positive for r 2 /R 2 > 1/α. Using the first equation in (46), it is straightforward to show that 0 < r 2 /R 2 < 1/α (respectively, r 2 /R 2 > 1/α) is equivalent to 0 < a 2 /A 2 < 1/α (respectively, a 2 /A 2 > 1/α). When α = 1, the modulus defined by (58) coincides with the generalised shear modulus defined in [104, p. 174], and also in [15].…”
Section: Dynamic Radial-axial Deformation Of a Cylindrical Tubementioning
confidence: 99%
See 2 more Smart Citations
“…In [17] a stability analysis of the aneurysm solutions in the presence of a mean flow was undertaken and it was found that if the speed of the mean flow is large enough, then the aneurysm solutions may be spectrally stable. It was found in [18] that for membrane tubes with localized wall thinning there exist two families of bulging solitary waves, and the lower family with amplitudes increasing with the inflation pressure is spectrally stable. In the latter case, we can speak about the standing wave (not orbital) stability, because the problem has no translational invariance any more.…”
Section: Introductionmentioning
confidence: 99%